Left atrial appendage occlusion versus standard of care in patients with atrial fibrillation and a prior thrombo-embolic event despite oral anticoagulant therapy: a propensity score matched comparison. (3rd October 2022) - Maarse, M; Seiffge, D; Fierro, N; Tondo, C; Pracon, R; De Backer, O; Nielsen-Kudsk, J; Estevez-Loureiro, R; Benito-Gonzalez, T; Nombela-Franco, L; Arzamendi, D; Alla, V; et al.
Abstract: Introduction: Patients with atrial fibrillation (AF) that suffer from ischemic stroke despite oral anticoagulant (OAC) therapy have a very high risk of recurrent stroke and better prevention strategies are needed. Left atrial appendage occlusion (LAAO) is a promising secondary prevention strategy that may provide mechanical protection in patients that suffer from thrombo-embolic events under OAC. However, evidence showing effectiveness of LAAO in this population is scarce and the current international guidelines only consider LAAO in patients with a contra-indication for OAC. Purpose: To compare percutaneous LAAO to standard-of-care including continuing/switching anticoagulation therapy for secondary stroke prevention in patients with AF and a prior thrombo-embolic event and/or LAA thrombus under OAC therapy. Methods: The STR-OAC LAAO cohort is an international collaboration combining a selection of patients from multiple LAAO registries (22 participating centers). Patients that underwent percutaneous LAAO because of a thrombo-embolic event and/or LAA thrombus on OAC were included. Propensity score matching (optimal matching method, 1:1 ratio) with a previously published multi-center dataset of patients continuing/switching anticoagulation treatment after a thrombo-embolic event was performed to adjust for imbalances in age, sex, hypertension, diabetes mellitus and CHA2DS2-VASc score. The primary outcome was ischemic stroke. Time-to-event analysis was performed with Kaplan-Meier curves and Cox-proportional-hazard regression analyses. Results: A total of 404 patients underwent LAAO between 2010–2021 and were included in the STR-OAC LAAO cohort. Mean age was 72±9 years; 44% was female and mean CHA2DS2-VASc and HAS-BLED score were 4.8±1.7 and 2.5±1.4, respectively. Most patients received a Watchman or Amplatzer device (53% and 43%). Oral anticoagulation was discontinued after LAAO at discharge or after confirmation of adequate LAA closure at 1–3 months follow-up in 44% or 20%, respectively. The remaining 35% of patients continued OAC after LAAO as an adjunctive strategy. All LAAO patients were propensity-score matched and included in the primary outcome analysis. Baseline characteristics were well balanced after matching (Table 1). During follow up including 1406 patient-years (LAAO 1007; control 399) a total of 61 patients experienced an ischemic stroke: 2.2% per patient-year in LAAO group versus 9.8% per patient-year in the control group. LAAO was associated with a significantly lower risk of ischemic stroke (HR 0.33, 95% CI [0.19–0.59], p<0.001) compared to standard-of-care (Figure 1). Conclusion: In this propensity-score matched study, LAAO was associated with a lower risk of ischemic stroke compared to standard-of-care in patients with a thrombo-embolic event and/or LAA thrombus despite OAC treatment. Randomized controlled trial data may further confirm the effectiveness of LAAO in this very high-risk population. Funding Acknowledgement: Type of funding sources: None.